2010
DOI: 10.1177/0022034509359403
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Dispersal: Mechanisms, Clinical Implications, and Potential Therapeutic Uses

Abstract: Like all sessile organisms, surface-attached communities of bacteria known as biofilms must release and disperse cells into the environment to colonize new sites. For many pathogenic bacteria, biofilm dispersal plays an important role in the transmission of bacteria from environmental reservoirs to human hosts, in horizontal and vertical cross-host transmission, and in the exacerbation and spread of infection within a host. The molecular mechanisms of bacterial biofilm dispersal are only beginning to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
654
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 736 publications
(672 citation statements)
references
References 161 publications
(232 reference statements)
8
654
0
10
Order By: Relevance
“…1). Hence, the dispersed cells were, until now, thought to be similar to planktonic cells and assumed to be easily eradicated by the host immune system and antimicrobials 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Hence, the dispersed cells were, until now, thought to be similar to planktonic cells and assumed to be easily eradicated by the host immune system and antimicrobials 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that biofilms are responsible for 65-80% of the infections occurring in the human body 5 , which, due to their persistence and chronic nature, place a massive burden on healthcare systems worldwide. Through dispersal processes, biofilms can spark new infections within the host and result in the transmission of bacteria between different hosts 4,6 . One medically relevant biofilm-forming bacterium is the opportunistic pathogen Pseudomonas aeruginosa, which is primarily known for its involvement in cystic fibrosis 7 , catheter-related infections 8 , and eye 9 and chronic wound infections 10 .…”
mentioning
confidence: 99%
“…In the presence of glass wool, planktonic cells were collected from the culture, and biofilm cells were collected from the glass wool by sonicating. Motility results indicated that a small proportion of biofilm cells (as early as 8 h) migrated much faster than the rest of the non-motile cells, which Figure 3a); however, these motile cells are probably derived from the biofilms as no highly motile cells arise in shaking flasks without biofilms, and cells frequently detach from biofilms (Kaplan, 2010). After 15 h, 24 h and 39 h of incubation, the proportion of highly motile cells increased for both biofilm and planktonic cells in contact with biofilms.…”
Section: Is5 Insertion Upstream Of Flhd þ Increases Diversity In Biofmentioning
confidence: 98%
“…Flagella are important for initial attachment in biofilms (Pratt and Kolter, 1998), for the mature structure , and for the dispersal of biofilms (Kaplan, 2010). Here, we tested whether IS5 is inserted upstream of flhD þ during biofilm development by screening biofilm cells for increases in motility.…”
Section: Is5 Insertion Upstream Of Flhd þ Increases Diversity In Biofmentioning
confidence: 99%
“…If nutrient sources persist, biofilms can grow into structures many orders of magnitude larger than individual cells. By contrast, if resources become depleted, bacteria can disperse back into the planktonic phase, presumably to encounter new locations with superior resource availability (Kaplan, 2010;Landini et al, 2010;McDougald et al, 2012). The ability of planktonic bacteria to adhere to naked surfaces and initiate biofilm formation has been studied extensively (Beachey, 1981;Palmer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%